PENGARUH DAYA TARIK IKLAN DAN FREKUENSI PENAYANGAN IKLAN TERHADAP INTENSI PEMBELIAN HAPPY CALL LEJEL HOME SHOPPING - Sri Nova Rina (Fakultas Ekonomi Universitas Tridinanti Palembang, 2014)
This research to assess The influence of advertising appeal and frequency of ads impact the intention to buy Happy Call Lejel Home Shopping (case study on Kelurahan Paku Sengkunyit. Population and sample in the study on Kelurahan Paku Sengkunyit, the sampling is determined by its own researchers use sampling techniques simple random sampling totaling 98 people, the analysis method used is Quantitative Methods using regression logistic analysis. Results of the analysis explains is = -8.612 + 1.338 + 1.363. The coefficient of determinationÃ‚Â Nagelkerke R Square of 0.833. The value show total contribusy follow explain independent variabel various dependent variabel. So this variation totaling can explained means that 83,3 % Ã‚Â actually influenced by the independent variable on advertising appeal and frequency of ads (who for detection or no). While the remaining 11,7% is influenced by other variables outside variables mentioned in this study. Ã‚Â Keywords : Advertising appeal, frequency of ads, the intention to buy.Ã‚Â